Morphological study of the spermatogenesis in the teleost Piaractus mesopotamicus - Da Cruz-Landim, Carminda [UNESP]; Abdalla, Fábio Camargo [UNESP]; Da Cruz-Höfling, Maria Alice (My University, 2003)
The spermatogenesis of Piaractus mesopotamicus was investigated under light and transmission electron microscopy. The specimens were captured from their natural environment (Rio Miranda and Rio Aquidauana, Pantanal Matogrossense, Brazil) during April and September. The results were compared with the spermatogenic data of specimens under captivity condition. In both conditions, P. mesopotamicus presented the typical spermatogenesis pattern of the teleost fishes, showing no significative differences. The spermatozoon was classified as type I, which has a globular head without acrosome, a short middle piece and a long tail constituted only by the flagellum. This type of spermatozoon is considered the basic type in fishes.
Keywords: Piaractus mesopotamicus; Spermatogenesis; Spermatogonia; Spermiogenesis; Teleostei